Comparison and evaluation of supercritical CO2 cooling performance in horizontal tubes with variable cross‐section by field synergy theory. (23rd May 2022) - Hao, Junhong; Ju, Chenzhi; Li, Chao; Tian, Liang; Ge, Zhihua; Du, Xiaoze
Summary: The cooling/heating performance improvement of supercritical carbon dioxide (sCO2 ) in heat exchange tube with changing cross‐section is significant and crucial for solar‐driven advanced thermal systems' application and development. The study introduced and constructed straight, diverging, and converging horizontal tubes with the changing cross‐section. The analyzation and evaluation of the sCO2 cooling performance used the combination of SST k‐ω turbulence model‐based numerical method and the field synergy theory, including the influence of tube cross‐sectional shape, inlet pressure and temperature on the cooling performance. As these simulation results indicate, the converging tube can enhance the flow field's synergy and increase the heat transfer ability by 13.15% under cooling conditions. Nevertheless, the heat transfer ability of the sCO2 decreases in the diverging tube under cooling conditions. Besides, the total heat transfer rate rises and the surface heat transfer coefficient has the opposite trends when the inlet temperature increases. Meanwhile, when inlet pressure varies from 11 to 12 MPa, the total heat exchange and surface convective heat transfer coefficient are the maximum. In conclusion, a converging horizontal tube and a suitable inlet pressure can effectively improve the cooling performance of the sCO2 . The converging cross‐section design will provide an alternative for its application in advanced thermal systems. Abstract : The converging tube can effectively improve the level of synergy of the flow field in the tube, which can enhance the heat transfer coefficient of the supercritical carbon dioxide under cooling conditions.